EFFECT OF VOLUME FRACTION OF GENETICALLY MODIFIED ORGANISM (GMO) SUGARCANE BAGASSE FIBER ON THE MECHANICAL PROPERTIES AND MORPHOLOGY OF BIOCOMPOSITE - Anuary Dwi Rosyid, Wafa Prasetia; Sakura, Rahma Rei; Djumhariyanto, Dwi; Asrofi, Mochamad; Setyawan, Digdo Listyadi; Sugiharto, Bambang; Junus, Salahuddin; Dwilaksana, Dedi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2023)
Science and technology are currently developing in all fields, such as vehicle construction, building construction, industry, and materials engineering. Especially in the field of material engineering used for the manufacture of composite materials. Currently the transition of materials from metal to composites is also in great demand in various fields including in the automotive, transportation, shipping, aerospace, health, and various other fields. In the components of a vehicle, the components that have the most potential to be reduced are the main structural components, namely the floor, body, and ribs. Efforts to reduce the weight of the material in these components are carried out to reduce the amount of fuel consumption, so the ratio of strength and density of a material is one of the important properties that needs to be considered. This study used the hand lay up method with a comparison of volume fraction variations of 15%: 85% and 20%: 80%. With the aim of adding volume fractions with optimal combinations, it is hoped that the tensile strength will get better. The highest average tensile strength is with a volume fraction ratio of 15%: 85% of 19.04 MPa. While the lowest average tensile strength is with a volume fraction ratio of 20%: 80% of 17.78 MPa. It can be concluded that with increasing fiber volume fraction, the tensile strength decreases. This happens because there are several defects in the form of holes and voids which indicate poor bonding between the fibers and the matrix. Keywords: PRG sugarcane fibers, volume fraction, epoxy, tensile properties